Double band gap gradients in sequentially processed photovoltaic absorbers from the Cu(In, Ga)Se2‐ZnSe pseudobinary system. (8th November 2017) - Kondrotas, Rokas; Oliva, Florian; Alcobe, Xavier; Izquierdo‐Roca, Victor; Perez‐Rodriguez, Alejandro; Saucedo, Edgardo; Pistor, Paul
Abstract: Wide band gap Cu(In, Ga)Se2 ‐ZnSe (CIGZSe) thin films have been synthesized using a sequential process, with the objective to demonstrate the possibility to tune the band gap and introduce double gradients playing with the content of Ga at the back and Zn at the front. In a first approach, we start by varying the 3‐valent cationic composition of the system, and then we modify the reactive annealing conditions in order to understand and control the elemental gradients. Structural, compositional, and morphological properties of the corresponding absorbers were analysed by X‐ray diffraction, Raman spectroscopy, energy dispersive spectrometer, Auger spectroscopy, and scanning electron microscopy. Solar cells were fabricated and characterized, focusing on the identification of the most promising cationic composition. The compounds from the complex Cu(In, Ga)Se2 ‐ZnSe system can adopt either the chalcopyrite or sphalerite phases depending on the [Zn]/[metals] and [Ga]/([Ga] + [In]) ratios. We demonstrate that Ga naturally diffuses towards the back region forming a Ga‐rich, wide band gap chalcopyrite phase at the rear contact, as is commonly observed for a Cu(In, Ga)Se2 synthesized via selenization process. On the contrary, Zn is preferably accumulated at the surface, forming wide band gap sphalerite Cu(In, Ga)ZnSe3 phases with high Zn and very low Ga contents at the surface. This opens an additional way to control the surface's band gap. With this approach, the formation of a doubly graded band gap profile with Ga‐rich layers at the back and Zn‐rich layers at the front is demonstrated in a single selenization step, showing promising efficiency and open circuit voltage values (up to 6.7% and 709 mV, respectively). Abstract : A double band gap gradient was obtained via single‐step selenization of In/CuGa/Zn metallic precursor. The preferable formation of CuInZnSe3 phase leads to the Zn‐rich surface and Ga‐rich back, increasing the band gap of absorber at the interfaces. Optimal selenization temperature was found to be 550°C.